DETEKSI AWAL, MANIFESTASI ORAL DAN PENATALAKSANAAN PERIODONTAL PADA PASIEN LEUKEMIA – SEBUAH TINJAUAN - Budi Budi; Irma Ervina (Universitas Baiturrahmah, 2021)
Introduction: Systemic diseases such as leukemia can manifest on the periodontium. The symptoms of this disease can be varied such as gingival enlargement, bleeding, oral ulceration, petechiae, mucosal pallor, noma, and trismus, but most clinicians are unaware of these conditions. This literature study purposed to review the literature concerning the oral manifestations and periodontal managements consideration of patients with leukemia. Review: The most frequent oral manifestations associated with leukemia are represented by the paleness of oral mucosa or abnormal color of the gum, petechiae, ecchymosis, bleeding associated with painless gingival hyperplasia, hemorrhage, ulcerative necrotic lesions, and buccal infections. Clinicians should take precautions when encountering those symptoms, such as referring the patient to specialized professionals. Besides that, clinicians should have a certain protocol to maintain the oral health of patients and to prevent complications that may occur from dental procedures. Patients with leukemia have a bleeding tendency and increased risk of infection which required special attention on periodontal and dental management to prevent the development of opportunistic infections and other complications. However, many patients are unaware of their disease and clinicians hold a pivotal role to identify leukemia through oral manifestations and giving feasible dental management. Conclusion: This review describes the oral manifestation of leukemia, which might be useful in early diagnosis. By knowing the diagnosis, clinicians should concern about special considerations in providing dental treatment to patients with leukemia.